2003
DOI: 10.1046/j.1523-1755.2003.00900.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of body water, fat-free mass, and body fat in patients on peritoneal dialysis by anthropometric formulas

Abstract: Anthropometric formulas currently in existence can provide only approximations of body composition and may be the sources of large errors in evaluating body composition in peritoneal dialysis patients. The potential errors include estimates of body water. These errors may alter the interpretation of urea kinetic studies in certain categories of peritoneal dialysis patients (e.g., obese subjects).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…This result agree with previous studies showing that anthropometry and BIA prediction equations used for TBW and body composition have the tendency to be population-specific and that inappropriate used of published prediction equations can lead to systematic errors and inaccurate estimations [26,27]. In this regard, Tzamaloukas et al [28] showed that each anthropometric measurement included in anthropometric equations for the prediction of body composition estimate a unique body composition which is for the average subject of the population in whom the equations were developed, while Haroun et al [29] showed for the BIA model that variation of the relative body geometry between ethnic groups confound the relative distribution between weight and impedance among limb and trunk. However, apart from biological variations, errors in the measurements could also contribute to the bias between measured and predicted TBW by BIA.…”
Section: Discussionsupporting
confidence: 92%
“…This result agree with previous studies showing that anthropometry and BIA prediction equations used for TBW and body composition have the tendency to be population-specific and that inappropriate used of published prediction equations can lead to systematic errors and inaccurate estimations [26,27]. In this regard, Tzamaloukas et al [28] showed that each anthropometric measurement included in anthropometric equations for the prediction of body composition estimate a unique body composition which is for the average subject of the population in whom the equations were developed, while Haroun et al [29] showed for the BIA model that variation of the relative body geometry between ethnic groups confound the relative distribution between weight and impedance among limb and trunk. However, apart from biological variations, errors in the measurements could also contribute to the bias between measured and predicted TBW by BIA.…”
Section: Discussionsupporting
confidence: 92%
“…TBW was predicted equally well and without systematic deviations in obese and nonobese, tall and short, and North American and German children, as well as in randomly selected subsets of the cohort. Although the predictive power of the new equations was superior to previous anthropometric formulas that were derived in healthy children, it should be kept in mind that even with the optimized formula, the 95% confidence interval for TBW predictions is as high as Ϯ4.4 L. Because of the physiologic and pathologic variability of body composition and fluid balance outlined above, it may be impossible to reduce further this residual variance of estimation if only height and weight data are available (20,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 90%
“…Even at normal body weight, the margin of error of the anthropometric formulas estimating body water is in the order of a few liters. Used in subjects with substantial water deficits, these formulas systematically overestimate body water [61][62][63][64]. This was our reason for basing the estimates of body water on the normal euglycemic state in this report.…”
Section: Limitationsmentioning
confidence: 98%